Theorems of existence and uniqueness for pointwise-slant immersions in Kenmotsu space forms - Alhouiti, Noura (AIMS mathematics, 2024)
The present paper aims to demonstrate the theorems of existence and uniqueness for pointwise slant immersions in Kenmotsu space forms. Some substantial results are given in this direction. Also, we offer non-trivial examples of pointwise slant submanifolds of an almost contact- metric manifold.